Facile air-oxidation of N-homopiperonyl-5,6-dimethoxyhomophthalimide: simple and efficient access to nuevamine - Wakchaure, Prasad B.; Easwar, Srinivasan; Puranik, Vedavati G.; N. P. Argade (Tetrahedron, 2008)
A facile six-step synthesis of naturally occurring (+/-)-nuevamine with 55% overall yield has been described, starting from methyl 2-(6-formyl-2,3-dimethoxyphenyl)acetate via the quantitative benzylic air-oxidation of the corresponding N-homopiperonyl-5,6-dimethoxy-homophthalimide to N-homopiperonyl-5,6-dimethoxyisoquinoline-1,3,4-trione as the key reaction, followed by base catalyzed regioselective alcoholysis of the trione with ring contraction, acid catalyzed dehydrative ring closure of the formed lactamol and decarboxylation pathway. (C) 2007 Elsevier Ltd. All rights reserved.

Synthesis of the reported protoberberine gusanlung D - Wakchaure, Prasad B.; Easwar, Srinivasan; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from homopiperonylamine or phenethylamine with homophthalic anhydride or 3,4-methylenedioxyhomophthalic acid, respectively, facile syntheses of the reported structures of (+/-)-gusanlung D and (+/-)-isogusanlung d were accomplished via regioselective reductive dehydration of the corresponding homophthalimides followed by an intramolecular acid-catalyzed or radical cyclization pathway. Starting from the corresponding suitably ortho-halogenated homophthalimides, the syntheses of dehydrogusanlung and dehydroisogusanhing D were completed via regioselective reductive dehydration followed by an intramolecular Heck coupling reaction as the key steps. The analytical and spectral data obtained for all four synthetic compounds differed from the reported data for natural gusanling D, and therefore the structural assignment of the natural product needs to be revised.
Keywords: gusanlung D; Heck reaction; homophthalic anhydride; homopiperonyl amine; reductive dehydration